Pengaruh Dana Alokasi Umum, Pendapatan Asli Daerah, dan Kinerja Keuangan Terhadap Belanja Modal Jawa Barat - Hidayat, Taufik (Jurnal Akuntansi Bisnis Pelita Bangsa, 2024)
Capital expenditure is part of regional expenditure which is used to budget expenditures made in the context of procuring fixed assets and other fixed assets which have a useful life of more than 12 (twelve) months, are used in local government activities and is a regulated minimum capitalization of fixed assets. in regional regulations. Factors that affect capital expenditure include the influence of general allocation funds (DAU), regional original income (PAD), and regional government financial performance as a source of financing as well as the measurement of regional financial performance in the implementation of capital expenditure both for the smooth running of government affairs and for improving facilities and infrastructure public. Financial performance in this study is proxied by the independence ratio, the PAD effectiveness ratio, the degree of fiscal decentralization, and the dependency ratio. The purpose of this study was to examine the effect of general allocation funds (DAU), regional original income (PAD), and local government financial performance on capital expenditure. This research is quantitative using SPSS version 26 software. It uses secondary data with data collection techniques using the documentary method. It uses a total sampling technique so that 81 samples consisting of 27 District and City Governments in West Java Province are obtained for the period 2019–2021. The results found that PAD and DAU partially significantly affected capital expenditure. Regional Government Financial Performance in the form of Dependency Ratio and Fiscal Decentralization Ratio partially has a significant effect on capital expenditure. Meanwhile, the Regional Government's Financial Performance in the form of the Independence Ratio and the PAD Effectiveness Ratio partially have no impact on Capital Expenditures.